Evaluation of the Effectiveness of Local Original Revenue Management in Supporting the Financial Performance of the Regional Government at the Office of the Regional Financial and Revenue Management Agency of South Nias Regency - Lase, Freddywan; Hulu, Perlindungan Faebuadodo (Amkop Management Accounting Review (AMAR), 2025)
This research analyzes the financial performance and the effectiveness of Local Original Revenue (PAD) management in the South Nias Regency Government. Using a qualitative approach, data were collected through in-depth interviews, observation, and documentation from four purposively selected informants: the Head of the Revenue Planning and Evaluation Division, the Head of the Assessment Collection and Objection Sub-Division, BPKPD staff, and business taxpayers. Findings indicate significant PAD recovery in 2025, reaching IDR 38.15 billion or 149.25% of the target. However, this achievement was driven by unsustainable incidental factors, including refunds for overpayments on goods and services totaling IDR 15.6 billion. The regional independence ratio was only 2.59% ("Very Low" category), indicating extreme dependence on central government transfers, with transfers exceeding 97%. PAD management faces structural constraints: low public awareness and compliance, untapped potential, ineffective manual collection systems, and insufficient collection frequency. A critical disparity exists between management perception and reality—Hotel Service Tax, perceived as the main PAD base, accounts for only 0.20%. In comparison, the actual most significant contributors are Electricity Consumption Tax (8.13%), Restaurant Tax (5.72%), and Mineral and Coal Tax (3.58%). Overall, PAD management appears "Very Effective" at 149.25%, but this is misleading due to incidental factors. Regional Retribution achieved only 50.47% ("Ineffective"), indicating the need for fundamental improvements to the collection system.